Differences in individual behavior and trophic niche of the red wood ant Formica aquilonia from urban and natural habitats: a case study in Novosibirsk region (West Siberia, Russia) - Ivan K. Iakovlev; Aleksei A. Maslov (Acta Biologica Sibirica, 2025)
Behavior plays a key role in the ability of animals to adapt to human-induced environmental change, although the consistency of these behavioral changes and their links to ecological niche are less clear. In this study, we examined the effects of habitat type and season on behavioral variation, trophic isotopic niche, and their relationships in the ant Formica aquilonia, a keystone species of forest communities in North Eurasia, collected from an urban forest park and a natural forest in spring and autumn. We found that exploratory activity was lower in urban than in natural forest ants. Aggression scores towards competitors (Lasius fuliginosus, L. niger) were similar in both habitats, but urban ants interacted longer with L. niger. Individual ant responses were positively correlated as an aggression-boldness syndrome (more aggressive individuals are more exploratory) in the natural habitat, but not in the urban environment, where the association between aggression and exploration was negative in autumn and decoupled in spring. The trophic niche of the ants differed between the habitats, expressed by lower δ15N and δ13C values in urban ants. It indicates that ants in the urban park fed at a lower trophic level and presumably consumed less tree-related resources than in the natural forest. Exploratory activity was positively correlated with δ13C value, suggesting a possible link between personality traits and ant diet. Our results on ants support findings on human-induced behavioral changes in vertebrates and highlight the need for further studies on the adaptation of wood ants to life in urban environments.